Unified M-Learning Model through Interactive Education Satellite:A Proposal for an Arab Homeland Education Satellite - Issa, Ghassan; Hussain, Shakir M.; AlBahadili, Hussain (International Journal of Interactive Mobile Technologies (iJIM), 2011)
In this paper, we propose a unified and interactive mobile learning (M-Learning) model to help with expanding and spreading education in the Arab Homeland countries. The model utilizes a new competitive spot beam satellite communication technology, which enables efficient channel allocation, where communication channels can be allocated to specific and precise areas. The proposed model is referred to as the interactive Arab education satellite (IAESat).The communication satellite can efficiently and effectively cover the entire Arab Homeland and reaches a wide area and mobile users that cannot be reached otherwise. The model implements existing interactivity components to enhance the learning process and meet international standards in education.